Analisis Perlakuan Akuntansi Aset Tetap pada RSUD Dr. Adhyatma, MPH Provinsi Jawa Tengah - Eko Cahyono; Agus Hariyanto (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to determine the accounting treatment for fixed assets at Dr. Adhyatma Regional General Hospital, MPH, Central Java Province, and to determine whether the accounting treatment for fixed assets at Dr. Adhyatma Regional General Hospital, MPH, Central Java Province, complies with PSAP No. 07 concerning Fixed Asset Accounting. This study used a qualitative descriptive research method, using triangulation (a combination of observation, interviews, and documentation) as data collection techniques at Dr. Adhyatma Regional General Hospital, MPH, Central Java Province. The results of this study indicate that the accounting treatment for fixed assets at Dr. Adhyatma Regional General Hospital, MPH, Central Java Province, in terms of classification, recognition, measurement, cost components, post-acquisition expenditures, depreciation, retirement, and disposal, complies with PSAP No. 07 concerning Fixed Asset Accounting. Disclosure of fixed assets regarding the reconciliation of the recorded amount at the beginning and end of the period and depreciation information including the depreciation value, gross recorded value and accumulated depreciation at the beginning and end of the period is in accordance with PSAP Number 07 of 2010 concerning Fixed Asset Accounting. However, for the basic information on the valuation used to determine the recorded value, depreciation information in the form of the depreciation method used and the useful life or depreciation rate used is not in accordance with PSAP Number 07 of 2010 concerning Fixed Asset Accounting.